2009
DOI: 10.1080/15299730902956838
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in Borderline Personality Disorder: A Detailed Look

Abstract: The objective of the present study was to assess in detail the whole spectrum of normal and pathological dissociative experiences and dissociative disorder (DD) diagnoses in borderline personality disorder (BPD) as diagnosed with the Revised Diagnostic Interview for Borderlines. Dissociation was measured comprehensively in 21 BPD outpatients using the Structured Clinical Interview for DSM-IV Dissociative Disorders-Revised, the Multidimensional Inventory of Dissociation (MID), the Dissociative Experiences Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 55 publications
7
56
0
4
Order By: Relevance
“…In the study by Korzekwa, Dell, Links, Thabane, and Fougere (2009), almost all BPD patients reported dissociative symptoms, and the majority of BPD patients met criteria for dissociative disorder diagnoses. Dissociative symptoms have not only been found to be elevated in psychiatric disorders that include dissociative symptoms in their diagnostic criteria (e.g., BPD and posttraumatic stress disorder , DSM-IV;American Psychiatric Assocation, 2000), but also in anxiety and panic disorders (Ball, Robinson, Shekhar, & Walsh, 1997), affective disorders (Oedegaard et al, 2008), and obsessive-compulsive disorder (Watson, Wu, & Cutshal, 2004).…”
mentioning
confidence: 96%
“…In the study by Korzekwa, Dell, Links, Thabane, and Fougere (2009), almost all BPD patients reported dissociative symptoms, and the majority of BPD patients met criteria for dissociative disorder diagnoses. Dissociative symptoms have not only been found to be elevated in psychiatric disorders that include dissociative symptoms in their diagnostic criteria (e.g., BPD and posttraumatic stress disorder , DSM-IV;American Psychiatric Assocation, 2000), but also in anxiety and panic disorders (Ball, Robinson, Shekhar, & Walsh, 1997), affective disorders (Oedegaard et al, 2008), and obsessive-compulsive disorder (Watson, Wu, & Cutshal, 2004).…”
mentioning
confidence: 96%
“…Recent research has documented that for a significant proportion of these cases, dissociative experiences extend the scope of transient symptoms and warrant the diagnosis of a dissociative disorder (Korzekwa, Dell, Links, Thabane, & Fougere, 2009;Sar, Akyuz, Kugu, Ozturk, & Ertem-Vehid, 2006;Sar et al, 2003). Hence, dissociative disorders and BPD are two partially overlapping syndromes on the spectrum of trauma-related psychopathologies (Korzekwa et al, 2009;Ross, 2007;Sar et al, 2003Sar et al, , 2006.…”
mentioning
confidence: 98%
“…Patients with BPD often suffer from dissociative states [125], which are known to influence learning and memory [126,127,128,129,130,131]. One study showed remarkable neuropsychological deficits in BPD patients with pathological dissociation, including attention, working memory, executive functioning, long-term memory, and general cognitive abilities, while BPD patients without pathological dissociation only showed deficits in executive functioning [132].…”
Section: Influence Of Affective State On Memory Performancementioning
confidence: 99%